SISTEM DETEKSI OTOMATIS JAMUR KULIT PADA PUNGGUNG MANUSIA MENGGUNAKAN SUPPORT VECTOR MACHINE - Helena Dorothea Mbura; Yampi R Kaesmetan (Jurnal Publikasi Manajemen Informatika, 2025)
Skin fungus (dermatomycosis) is an infection caused by various types of fungi that develop in the epidermal layer of human skin. This infection is often difficult to detect early, especially if it occurs in hard-to-reach areas such as the back. Therefore, this study aims to develop an automatic detection system for skin fungus on the human back using the Support Vector Machine (SVM) method in digital image processing. This system is designed to help medical personnel and the general public in early detection of skin fungal infections more quickly and accurately. The methods used include image feature extraction using the Canny Edge Detection technique and classification using SVM. With the website-based system, users can upload photos of their skin to be analyzed automatically without the need for a direct visit to a health facility. The results show that this approach has a high accuracy rate in identifying skin fungal infections. Thus, this research is expected to contribute to improving the effectiveness of skin fungal disease detection and treatment in the community.